Experimental Estimation of the Friction Coefficients Due to Deviation (k) and Curvature (μ) in Post-Tensioned Cables through Electronic Instrumentation - Poveda Salamanca, Carlos Eduardo (2025)
This paper conducted a pilot estimate of the friction coefficients for deviation and post-curvature of wires of different pipeline materials, of galvanized metal and plastic, through its electronic instrumentation.  For this purpose, two post-stressed concrete beams were built, whose instrumentation was performed using a data acquisition system and strain gages, the ones which were used to determine the variation of the unit strain values, and therefore the tension losses of the cables, along their length. The designe was conceived as a slab-beam type pedestrian crosway.   Knowing the geometry and the tension at each point of the cables, the ranges of the friction coefficients were estimated for both, unintentional deviation (k) and curvature (μ), which were compared with national and international standards. In this research, it was concluded that the ranges of the friction coefficients of metallic pipelines for unintentional deviation (k) are similar to those recommended by the standards, while the coefficients for curvature (μ) are higher.  For plastic products, the values of their coefficients of friction (µ k), estimated in this research are innovative, because they are not included in the standards, thus it is a contribution to the national engineering. This work is the base for further research and also to update the national standards. This project was possible thanks to the support of VSL International and CEMEX, generating innovation and technology transfer to the industry and the society.